Cik Upik Application as Learning Media to Identify and Describe the Hikayat Values - Hary Soedarto Harjono; Bambang Hariyadi; Priyanto; Pranowo Yugo (Universitas Pendidikan Ganesha, 2023)
The basic competence of students to be able to describe the values and content of hikayat or folklore, which is one of the achievement targets for learning literature in high school cannot be grasped optimally without the support of appropriate learning media. Therefore, the main objective of this research is to develop learning media in the form of an application that can be used to explore and describe the values included in the Cik Upik folklore, which is a form of Malay oral literature. In doing so, research and development model of ADDIE (Analysis-Development-Design-Implementation-Evaluation) is carried out by involving subject matter experts in Indonesian language and folklores and media experts as validators for instrument and product development. In addition, an Indonesian teacher and 10 class X students at a high school participated as research subjects. In the needs analysis stage, a questionnaire was used to explore the needs of teachers and students, which were used as a consideration in designing and developing learning media. The results of the validation of material experts and media experts as well as the responses of teachers and students show that the learning media applications developed in this study were declared valid with very good qualifications. This implied that the learning media application developed in this research and development is very feasible to be used as a learning medium to describe the values included in folklore.